ONTOLOGICAL ASPECTS OF HUMAN’S SPIRITUAL WORLD (Academicia Globe: Inderscience Research, 2022)
In this article, the ontological issues, peculiarities and problems of human spiritual existence are analyzed. The issues of the objective and subjective influence of the rise and crisis of human spiritual life, the specific influence of spirituality on the external and internal life of man are philosophically illuminated. The causes and consequences of the human spiritual crisis, the level of spiritual maturity, were analyzed.